Asymmetry in market efficiency across economic states: explanation and implication. (1st January 2012) - Hammami, Yacine
The empirical financial literature has recently suggested that the US stock market might be efficient in bad times and inefficient in good times. This article explains why some psychological phenomena such as wishful thinking, overconfidence and the house money effect might cause deviations from full rationality principally in good times and not in bad times. Furthermore, this article gives several reasons why the arbitrage process might be effective in bad times and limited in good times. These results are important both for policymakers and for portfolio management.